2010
DOI: 10.1080/01496395.2010.494090
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium Solubility in Simulated Savannah River Site Waste Solutions

Abstract: To address the accelerated disposition of the supernate and salt portions of Savannah River Site (SRS) high level waste (HLW), solubility experiments were performed to develop a predictive capability for plutonium (Pu) solubility. A statistically designed experiment was used to measure the solubility of Pu in simulated solutions with salt concentrations and temperatures which bounded those observed in SRS HLW solutions. Constituents of the simulated waste solutions included: hydroxide (OH No discernable time d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Comparison of the results to predictions generated using statistically-based models developed at SRNL, [5] revealed that the models predict the solubility relatively well in some cases (particularly for relatively short time scales) but not in others. The uranium model predicted solubilities very similar to the observed values at 50-100 days for Samples 2, 3 and 5.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparison of the results to predictions generated using statistically-based models developed at SRNL, [5] revealed that the models predict the solubility relatively well in some cases (particularly for relatively short time scales) but not in others. The uranium model predicted solubilities very similar to the observed values at 50-100 days for Samples 2, 3 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…Part of these studies involved the determination of actinide solubilities in various simulated SRS process solutions of prototypical chemical composition. [4][5] Studies by other groups have focused on the determination of actinide solubilites in simulated Hanford waste solutions [6] and on determining actinide speciation and solubility in other highly alkaline solutions [7][8][9][10] .…”
mentioning
confidence: 99%
See 3 more Smart Citations